Scattering processes of nuclides 3He, 4He with E = 50,5 and 60 MeV on 24Mg nuclei - Duisebayev, A.; Duisebayev, B.A.; Zholdybayev, T.K.; Sadykov, B.M. (Recent Contributions to Physics, 2013)
New experimental results on elastic and inelastic scattering of nuclides 3He, 4Не at energies 50 and 60 MeV of for 24Mg at excited state 1.37 and 4.12 MeV are presented. The literature review is done. The analysis of cross-sections of elastically scattered nuclides 3He, 4Не on studied nucleus was performed using standard optical model with Woods-Saxon potential with separated form-factors of real and imaginary parts. The optimal values of inter-nuclear interaction potentials are obtained. As a criterion for matching the results of theoretical calculations with experimental data the minimization of the χ2 values and the values of the volume integrals of the real part of the optical potential were used. Analysis of cross sections of inelastic scattered ions of helium nuclei 24Mg was carried out using the distorted waves with form-factor of a macroscopic collective excitation using optimal optical potential parameters obtained from elastic scattering. The analysis by the method of coupled channels, where the calculation was performed taking into account both the elastic and inelastic channels was done. The quadrupole deformation parameter β2 = 0.36 – 0.34 of nucleus 24Mg was defined.